Empowering rural learners: A micro-credential program for skills development - Sidah Idris; Kasim Hj. Mansor (International Journal of Business, Economics and Law, 2024)
A micro-credential learning can considerably improve rural learners’ social mobility by making educational options more accessible, flexible, and focused. By addressing the unique problems that these communities confront, stakeholders may help to create a more inclusive and equitable educational environment that benefits both individuals and local economies. This innovation study aims to develop a platform to accommodate rural learners in occupational certification. The certificate will be awarded by an industry or professional association to an individual demonstrating designated knowledge, skills, and abilities in a particular occupation. This study started with conducting surveys and focus groups discussion to understand the specific needs and interests of rural learners. Collaboration with local educational institutions, NGOs, and businesses helped to collect information and resources. The pilot study with a small group of learners aims to gather feedback and make necessary adjustments. This study expected to provide a platform that can provide learners with targeted, accessible education that meets their unique needs, such as equipping them with practical skills relevant to their community and fostering collaboration among learners to tackle local issues. The local community with local industries and organisations will match the in-demand skills such as agriculture, digital literacy, and entrepreneurship.